Being salvation atonement and soteriology in the theology of Karl Rahner - Peterson, Brandon R. (Fortress Press, 2017)
Being Salvation unfolds the role of Jesus Christ-his person and the work of atonement-within Rahner's theology, situating it in relation to other historical examples of representative soteriology (e.g., Irenaeus of Lyons and his notion of recapitulation) and to Rahner's more familiar sacramental soteriological categories. It gives special attention to Rahner's early studies of and writings on the Church Fathers, particularly Rahner's own untranslated and recently published dissertation, E latere Christi ("From the Side of Christ")